The Origins of the Name "Middle State" - Gawlikowski, Krzysztof (Czasopismo Prawno-Historyczne, 1980)
The term „Middle State" (Zhongguo) that the Chinese have used to name their homeland since antiquity and now, is, for sure, most special. Clearly, it comes neither from an ethnonym nor from a toponym as is the case with many other political entities, but it is connected with definite philosophies and world outlook. What is more, for more than two thousand years this term carried in its wake some ideological contents conventionally called as sinocentrism. Hence many questions arise: Why and since when have the Chinese nemed their country in this strange way? How their concepts of the state have evolved? Did they really believe, as is often claimed, from the dawning of their history that they inhabited "the world centre"? Since most of the various matters related to this central problem have not been studied in detail, it is not possible in every case to provide a fully satisfying answer to the questions posed above.